EFEKTIVITAS METODE DISKUSI DAN INVESTIGASI KELOMPOK DALAM MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATERI INTERAKSI MANUSIA DENGAN LINGKUNGAN DI SMP NEGERI 3 SUKOHARJO - Nurhayati, Kurnia (Pendidikan Geografi, 2014)
EFEKTIVITAS METODE DISKUSI DAN INVESTIGASI KELOMPOK DALAM MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATERI INTERAKSI MANUSIA DENGAN LINGKUNGAN DI SMP NEGERI 3 SUKOHARJO Kurnia Nurhayati1,*, Djoko Subandriyo2 dan Rita Noviani21Program Pendidikan Geografi PIPS, FKIP, UNS Surakarta, Indonesia2 Dosen Program Pendidikan Geografi PIPS, FKIP, UNS Surakarta, Indonesia*Keperluan korespondensi, HP : 085726513242, e-mail : kurnia.k5410032@yahoo.com ABSTRACT.The curriculum alteration from SBC (Education Unit Level Curriculum) to the 2013 curriculum has purpose on the improvement of students? critical thinking and activeness participation on teaching learning activity. This matter leads the teacher to find proper teaching strategy in order to gain the purpose of curriculum. SMP N 4 Sukoharjo is one of the schools which implement 2013 curriculum but, the learning strategy being implemented is not really relevant with the curriculum itself. The subject material being learnt on the 8th grade is Human and Environment Interaction. In order to improve the students? critical thinking and activeness, proper learning method being proposed is project based learning through group discussion and investigation. Based on the research purpose, this research used quasi experimental method. The research subject is students who sit on the VII E and VII F class at even semester, SMP N 3 Sukoharjo. Research object being chosen are learning outcome of the Social Science on human and environment interaction material by using group discussion and investigation on project based learning model. Data collection technique in this study was documentation, test, and observation. The data analysis was hypothesis test.Based on the data analysis and discussion, the conclusion are as follows : (1) there is significant difference of learning result between group investigation and discussion method related with Project Based Learning approach on Social Science with Human and Environment Interaction material at the VII grade students in even semester of SMPN 3 Sukoharjo 2013/2014 academic year , it was considered from the result of t test, in the amount of tcount > ttable or 6,186 > 1,67 (2) group investigation method in Project Based Learning tends to be more effective being implemented than discussion method. It was seen from the learning outcomes average of the students. Keyords : Project Based Learning. Discussion Method, Group Investigation Method, Process and Learning Outcomes